Injection molded lab-on-a-disc platform for screening of genetically modified E. coli using liquid–liquid extraction and surface enhanced Raman scattering. Issue 6 (16th February 2018) - Morelli, Lidia; Serioli, Laura; Centorbi, Francesca Alessandra; Jendresen, Christian Bille; Matteucci, Marco; Ilchenko, Oleksii; Demarchi, Danilo; Nielsen, Alex Toftgaard; Zór, Kinga; Boisen, Anja
Abstract : We present an injection molded lab-on-a-disc enabling quantification of bacterial metabolites in E. coli supernatant. Abstract : We present the development of an automated centrifugal microfluidic platform with integrated sample pre-treatment (filtration and liquid–liquid extraction) and detection (SERS-based sensing). The platform consists of eight calibration and four assay modules, fabricated with polypropylene using injection molding and bonded with ultrasonic welding. The platform was used for detection of a secondary bacterial metabolite ( p -coumaric acid) from bacterial supernatant. The obtained extraction efficiency was comparable to values obtained in batch experiments and the SERS-based sensing showed a good correlation with HPLC analysis.